The Effect of Applying Problem-Based Learning Model on Students’ Critical Thinking Ability Science Subjects in Grade V Elementary School - Tutik Hidayati; Dyah Purwaningsih (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
One of the problems faced by elementary school students is the difficulty of mastering the subject matter being taught. Efforts to increase mastery of the material were carried out by teachers, among others, by applying various varied learning models. The Problem Based Learning model is a learning model that is able to hone students' critical thinking. The purpose of this study was to analyze the effect of the Problem Based Learning model on science learning content on the critical thinking abilities. This study uses a quantitative approach to the experimental method. This research was conducted at elementary students using grade V as the research target for treatment by the Problem Based Learning learning model. The data analysis used was the t-test for sample correlation ratio data with the Wilcoxon Matched Pairs test analysis. The problem-based learning model to improve the critical thinking skills of science grade V elementary school students has a positive and significant effect. The results of this study conclude that hypothesis 1 (h1) is accepted. This shows that the Problem Based Learning model influences students' critical thinking ability, where students' critical thinking ability increase after being applied to a given subject.